Exploring Cybercrime – Realities and Challenges - Victoria Stanciu; Andrei Tinca (Journal of Accounting and Management Information Systems (JAMIS), 2017)
Cybercrime is a global, transnational serious problem that needs strong technical and legal responses. The information represents an important asset that must be secured and properly used as it provides the support for value creation and sustainable development. Being a valuable asset, the information is exposed to continuous and virulent attacks conducted by cybercrime groups and significant financial and human resources must be allocated to the cybercrime limitation. The purpose of authors' research was to get more knowledge about cybercrime and attacker's behavior and to develop a discussion on the cyber security and the means of its improvement. The research results attempt to provide useful recommendations on countermeasures against cybercrime and raise the awareness of companies' senior management and governments' representatives on cyber criminality.
Keywords: M15; 650; Information security; cybercrime; organized crime; cybercrime prevention